Caracterización del perfil Hematológico y Bioquímico del Ovino Criollo Ecuatoriano en la Provincia de Tungurahua - Barriga Perugachi, Evelin Paulina (2018)
The present work was carried out in the Pilahuin Parish, Canton Ambato - Tungurahua Province, with the objective of characterizing the hematological and biochemical profile of the Creole sheep in the Province of Tungurahua. Where were 30 blood samples analyzed of Creole sheep (16 females and 14 males). Seven hematological variables were evaluated (Hematocrit, Hemoglobin, Erythrocytes, VGM, MCH, CGMH and Platelets), 6 variables of the white series (Leukocytes, Neutrophils, Lymphocytes, Monocytes, Eosinophils and Basophils) which were analyzed by automated and manual techniques and 10 biochemical variables (Glucose, Urea, BUN, Creatinine, ALT, Total proteins, Calcium, Phosphorus, and Potassium) by the calorimetric and enzymatic method. For the data analysis, descriptive statistics were used analyzing the values of the mean, maximum values, minimum values and standard deviation using the Excel 2016 program. To assess the effect of sex on the variables described above, the variance analysis was carried out using the Tukey test at 5% (p> 0.05). Where there were no significant differences for the variables of the hematological profile. However, a significant difference was recorded for the leukocyte, monocyte, and lymphocyte variables, observing an increase in their mean for the females. Regarding blood chemistry, only significant differences were observed for the phosphorus variable with a numerical difference of its mean for the males, according to previous studies it is confirmed that in the correlation of the calcium / phosphorus ratio where there are significant differences in relation to different parameters that they can change depending on the factors assigned to the place, climate, food and / or care corresponding to the biochemical profile.